2023
DOI: 10.1108/jfra-07-2022-0245
|View full text |Cite
|
Sign up to set email alerts
|

The effect of key audit matters on the audit report lag: evidence from Jordan

Abstract: Purpose This paper aims to explore the potential effect of key audit matters (KAM) on the audit report lag (ARL). In particular, it aims to discover whether the number of KAMs reported by an audit firm in Jordan is related to the length of its ARL. Design/methodology/approach The authors analysed data from the first three years of KAM reporting in Jordan (2017–2019) for 194 public listed Jordanian companies to examine the relation between the number of KAMs and the ARL, taking into account several control va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 96 publications
1
5
0
Order By: Relevance
“…This can be inferred from the fact that the number of KAM reported has increased. The findings of Abdullatif et al (2023) are validated by this research. They discovered that the increase in "going worry and impact of Covid-19" KAM in 2020 represents the worldwide economic implications of the travel prohibition caused by COVID-19 becoming obvious.…”
Section: Univariate Analysissupporting
confidence: 70%
See 3 more Smart Citations
“…This can be inferred from the fact that the number of KAM reported has increased. The findings of Abdullatif et al (2023) are validated by this research. They discovered that the increase in "going worry and impact of Covid-19" KAM in 2020 represents the worldwide economic implications of the travel prohibition caused by COVID-19 becoming obvious.…”
Section: Univariate Analysissupporting
confidence: 70%
“…Regarding the variable of the key audit matters ( KAM) , the mean (median) value is found 2.688 (1.457). The investigation showed that external auditors in Jordan confirmed 18% on average of KAM disclosers over the period after ISA-701 was implemented to improve audit transparency and reduce “information asymmetry” (Abdullatif et al , 2023). The moderating variable ( COVID ) does have an average (median) value of 0.50 (0.50).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study examines the potential relationship between KAM reporting and ARL (audit report lag) and its findings show that there is no statistically significant relationship between the number of KAMs reported by Jordanian audit firms and audit report lag. But, on the other hand, the research found statistically significant positive relationships between ARL and audit fees, audit firm size, giving a qualified audit opinion and company leverage and a statistically significant negative relationship between ARL and company profitability [126]. Changes in auditing reporting standards have also been supported by academic researchers [127,128] which agree that audit profession development is assured by the auditor credibility [129].…”
Section: Diagram (A)mentioning
confidence: 84%